Comparison of skeletal anchorage and tooth-borne maxillary protraction followed by fixed appliance in Class III malocclusion. (21st November 2019) - Lee, Sang-Hoon; Koh, Sang-Duck; Chung, Dong-Hwa; Lee, Jin-Woo; Lee, Sang-Min
Summary: Objectives: The purpose of this study was to compare the results of skeletal anchorage (SAMP) and tooth- borne (TBMP) maxillary protraction followed by fixed appliance in growing skeletal Class III patients. Materials and methods: Patients treated with maxillary protraction were selected and classified into two groups (SAMP: n = 19, mean age = 11.19 years; TBMP: n = 27, mean age = 11.21 years). Lateral cephalograms taken before treatment (T0), after the maxillary protraction (T1), and after the fixed appliance treatment (T2) were analysed and all variables were statistically tested to find difference between the two groups. Results: Compared to the TBMP, the SAMP showed significant forward growth of maxilla (Co-A point and SN-Orbitale) and improvement in intermaxillary relationship (ANB, AB to mandible plane, and APDI) after the overall treatment (T0–T2), with no significant sagittal changes in maxilla or mandible throughout the fixed appliance treatment (T1–T2). Limitations: In maxillary protraction, effects of skeletal anchorage were retrospectively compared with those of dental anchorage, not with Class I or III control. Conclusions and implications: After maxillary protraction, skeletal and tooth-borne anchorage did not cause significant differences in the residual growth of maxilla throughout the phase II treatment. Orthopaedic effects with skeletal anchorage showed appropriate stability in maxilla and intermaxillary relationship even after fixed appliance treatment.